(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2018)
Britain is a country that has a great history and influence in the history of other countries, both in economics, military, politics and it can be said that it was ‘a compulsion’ integration with the European Union. UK and EU relations did not always go smoothly. A lot of dynamics have occurred since the British joined in 1973 until the 2016 referendum decision was issued. The researchers’ interest in elaborating the phenomenon was outlined in a historical study of the dynamics between Britain and the European Union since integration until the Brexit decision. Especially to understand the process of British integration, the characteristics of the United Kingdom as a member and the support of the majority of Britains to decide Brexit.